In-depth review of delivery carriers associated with vaccine adjuvants: current status and future perspectives - Yarong Zeng; Feihong Zou; Ningshao Xia; Shaowei Li (Expert Review of Vaccines, 2023)
Introduction Vaccines are powerful tools for controlling microbial infections and preventing epidemics. To enhance the immune response to antigens, effective subunit vaccines or mRNA vaccines often require the combination of adjuvants or delivery carriers. In recent years, with the rapid development of immune mechanism research and nanotechnology, various studies based on the optimization of traditional adjuvants or various novel carriers have been intensified, and the construction of vaccine adjuvant delivery systems (VADS) with both adjuvant activity and antigen delivery has become more and more important in vaccine research. Areas covered This paper reviews the common types of vaccine adjuvant delivery carriers, classifies the VADS according to their basic carrier types, introduces the current research status and future development trend, and emphasizes the important role of VADS in novel vaccine research. Expert opinion As the number of vaccine types increases, conventional aluminum adjuvants show limitations in effectively stimulating cellular immune responses, limiting their use in therapeutic vaccines for intracellular infections or tumors. In contrast, the use of conventional adjuvants as VADS to carry immunostimulatory molecules or deliver antigens can greatly enhance the immune boosting effect of classical adjuvants. A comprehensive understanding of the various delivery vehicles will further facilitate the development of vaccine adjuvant research.